2016
DOI: 10.1093/jme/tjw202
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Survey forFrancisella tularensisandRickettsiaspp. inHaemaphysalis leporispalustris(Acari: Ixodidae) in Northern California

Abstract: Francisella tularensis and Rickettsia spp. have been cultured from Haemaphysalis leporispalustris Packard, but their prevalence in this tick has not been determined using modern molecular methods. We collected H. leporispalustris by flagging vegetation and leaf litter and from lagomorphs (Lepus californicus Gray and Sylvilagus bachmani (Waterhouse)) in northern California. Francisella tularensis DNA was not detected in any of 1,030 ticks tested by polymerase chain reaction (PCR), whereas 0.4% of larvae tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…maculatum (Wright et al, 2015). Additionally, although R. felis is primarily associated with cat fleas, it has been detected sporadically in ticks, which supports the data presented here (Ishikura et al, 2003; Jiang et al, 2012; Abarca et al, 2013; Soares et al, 2015; Roth et al, 2016). No transovarial transmission of R. rickettsii was identified for either tick species in the current study, consistent with previous results in which naĂŻve female ticks were refractory to transovarial transmission, despite massive infection in the ovaries of engorged females post-rickettsial exposure (Niebylski et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…maculatum (Wright et al, 2015). Additionally, although R. felis is primarily associated with cat fleas, it has been detected sporadically in ticks, which supports the data presented here (Ishikura et al, 2003; Jiang et al, 2012; Abarca et al, 2013; Soares et al, 2015; Roth et al, 2016). No transovarial transmission of R. rickettsii was identified for either tick species in the current study, consistent with previous results in which naĂŻve female ticks were refractory to transovarial transmission, despite massive infection in the ovaries of engorged females post-rickettsial exposure (Niebylski et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…By molecular techniques, R. felis has been detected in different flea species, mosquitoes, mites, and ticks (both Ixodid and Argasid). These tick species include Rhipicephalus sanguineus in Brazil, Spain, Chile, China, and the Philippines [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]; Rhipicephalus bursa in Turkey [ 22 ]; Rhipicephalus turanicus in Italy [ 23 ]; Haemaphysalis flava, Haemaphysalis kitasatoe, and Ixodes ovatus in Japan [ 24 ]; Haemaphysalis sulcata in Croatia [ 25 ]; Haemaphysalis leporispalustris in the United States [ 26 ]; Haemaphysalis sp. and Rhipicephalus microplus in Malaysia [ 27 ]; Heamaphysalis bancrofti in Australia [ 28 ]; Amblyomma maculatum in the United States [ 29 ]; Amblyomma cajennense , Amblyomma humerale, Amblyomma ovale , and Amblyomma sculptum in Brazil [ 14 , 30 , 31 , 32 ]; Ixodes granulatus in Taiwan [ 33 ]; Ixodes hexagonus in Italy [ 34 ]; Ixodes ricinus in Germany, France, Spain, Romania, and Serbia [ 35 , 36 , 37 , 38 , 39 , 40 ]; Dermacentor nitens in Brazil and Cuba [ 21 , 41 ]; and Dermacentor variabilis and Carios capensis in the United States [ 42 , 43 ] ( Table S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleic acid from R. felis and related R. felis-like organisms (RFLOs) has been detected in other hematophagous arthropods, including more than 40 species of fleas, ticks, and mosquitoes [4,10]. Field surveys have identified R. felis in wild-caught ticks [11][12][13] and laboratory studies have demonstrated R. felis was vertically transmitted by the American dog tick, Dermacentor variabilis, when adult ticks were exposed via capillary feeding [14]. More recently, in sub-Saharan African countries where R. felis has been reported as an emerging cause of unknown fever, R. felis has been detected in mosquitoes [3,15,16].…”
Section: Introductionmentioning
confidence: 99%